The state of lipid metabolism in patients with acute coronary syndrome and chronic kidney disease depending on glomerular filtration rate and smoking factor - O. V. Yadzhyn; T. M. Solomenchuk (Zaporožskij Medicinskij Žurnal)
Aim. To study the features of lipid metabolism disorders in patients with acute coronary syndrome (ACS), depending on glomerular filtration rate (GFR) and smoking factor.